2017
DOI: 10.1016/j.celrep.2017.09.092
|View full text |Cite
|
Sign up to set email alerts
|

Fumarate Hydratase Loss Causes Combined Respiratory Chain Defects

Abstract: SummaryFumarate hydratase (FH) is an enzyme of the tricarboxylic acid (TCA) cycle mutated in hereditary and sporadic cancers. Despite recent advances in understanding its role in tumorigenesis, the effects of FH loss on mitochondrial metabolism are still unclear. Here, we used mouse and human cell lines to assess mitochondrial function of FH-deficient cells. We found that human and mouse FH-deficient cells exhibit decreased respiration, accompanied by a varying degree of dysfunction of respiratory chain (RC) c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
70
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 72 publications
(87 citation statements)
references
References 33 publications
8
70
0
2
Order By: Relevance
“…This result is consistent with the increased motility of UOK262 cells, which has also been associated with epithelial to mesenchymal transition (EMT) ( Sciacovelli et al, 2016 ). Several GO terms related with mitochondrial processes, such as respiratory chain complexes, were down-regulated, consistently with the metabolic model predictions and previously observed decreased mitochondrial activity ( Sciacovelli et al, 2016 , Tyrakis et al 2017 ). We then assessed if changes in protein abundance of metabolic enzymes could be related with metabolic flux changes predicted by the model ( Supplementary Fig.…”
Section: Resultssupporting
confidence: 89%
“…This result is consistent with the increased motility of UOK262 cells, which has also been associated with epithelial to mesenchymal transition (EMT) ( Sciacovelli et al, 2016 ). Several GO terms related with mitochondrial processes, such as respiratory chain complexes, were down-regulated, consistently with the metabolic model predictions and previously observed decreased mitochondrial activity ( Sciacovelli et al, 2016 , Tyrakis et al 2017 ). We then assessed if changes in protein abundance of metabolic enzymes could be related with metabolic flux changes predicted by the model ( Supplementary Fig.…”
Section: Resultssupporting
confidence: 89%
“…A study on kidney tumours showed that the excess of fumarate upregulates the proto‐oncogene Abelson murine leukemia viral oncogene homolog 1 (ABL1), which in turn stimulates: mammalian target of rapamycin (mTOR)/HIF‐1α signalling promoting aerobic glycolysis; nuclear localization of nuclear factor (erythroid‐derived 2)‐like 2 (NRF2); and ROS detoxification (Sourbier et al , ). Intriguingly, the metabolic phenotype of FH‐deficient cells could allow the tumour to resist unfavourable conditions affecting mitochondrial function, such as hypoxia (Tyrakis et al , ). Other studies have also shown that FH‐deficient cells and tissues exhibit defects in the urea cycle and arginine metabolism, highlighting an important extra‐mitochondrial metabolic role of cytosolic FH (Adam et al , ).…”
Section: Oncometabolites and Their Related Metabolic Enzymesmentioning
confidence: 99%
“…Some of the selected mRNAs have been associated with the Krebs cycle or respiratory chain complexes. This is the case for Fahd1 (Pircher et al, 2015;Weiss et al, 2018), Lyrm5 (Floyd et al, 2016;Pagliarini et al, 2008), and Fh1 (Tyrakis et al, 2017). Interestingly, a reduction in Fh1 leads to mitochondrial respiratory chain defects, particularly in the complex I and II (Tyrakis et al, 2017).…”
Section: Transcript Analysis Reveals Oxidative Phosphorylation As a Cmentioning
confidence: 86%
“…This is the case for Fahd1 (Pircher et al, 2015;Weiss et al, 2018), Lyrm5 (Floyd et al, 2016;Pagliarini et al, 2008), and Fh1 (Tyrakis et al, 2017). Interestingly, a reduction in Fh1 leads to mitochondrial respiratory chain defects, particularly in the complex I and II (Tyrakis et al, 2017). Other validated mRNAs, such as Lonp1 or Atg13, have a mitochondrial protease function (Bota & Davies, 2016;Hoshino et al, 2014) or are linked to autophagy of the mitochondrion (Kaizuka & Mizushima, 2016), respectively.…”
Section: Transcript Analysis Reveals Oxidative Phosphorylation As a Cmentioning
confidence: 94%